Impact Behavior of Multi-Layered UHMWPE Vests Reinforced with Titanium and PVC for Ballistic Protection - Muzhaffar Effendi, Nabil; Sastranegara, Azhari; Hernawan, Rendi; Anggraini, Lydia (Faculty of Engineering and Technology, Sampoerna University, 2025)
Achieving lightweight and high-performance bulletproof vests is essential for military and law enforcement, where balancing mobility and ballistic resistance is critical. This study investigates the ballistic performance of multi-layered Ultra-High Molecular Weight Polyethylene (UHMWPE) vests reinforced with titanium (Ti6Al4V) and polyvinyl chloride (PVC). Two innovative vest configurations were evaluated following National Institute of Justice (NIJ) Standard-0101.04 ballistics tests and simulated using the Finite Element Method (FEM). Experimental findings indicated that while Vest 1 significantly absorbed impact energy, it failed to prevent projectile penetration. In contrast, Vest 2, incorporating additional titanium and polymer layers, effectively mitigated the penetration of 9 mm Full Metal Jacket (FMJ) projectiles while maintaining a safe back-face signature (BFS). The FEM simulation results demonstrated strong agreement with the experimental data, validating the effectiveness of multi-material layering in enhancing ballistic resistance. This research presents a strategic integration of titanium and polymer composites designed to achieve superior ballistic resistance while maintaining lightweight properties. These findings provide valuable insights for developing advanced body armor designs suitable for high-performance military and law enforcement applications.